Comparison of Macintosh and AirtraqTM laryngoscopes in obese patients placed in the ramped position - Ranieri, D.; Filho, S. M.; Batista, S.; do Nascimento, P. [UNESP] (Wiley-Blackwell, 2012)
This study compared intubation conditions produced by the Macintosh and AirtraqTM laryngoscopes when used in obese patients in the ramped position. One hundred and thirty-two patients having bariatric surgery were placed in the ramped position and randomly assigned to have their tracheas intubated using either the Macintosh (n = 64) or an Airtraq (n = 68) laryngoscope. Mean (SD) intubation times were 37 (23) s and 14 (3) s for Macintosh and Airtraq, respectively (p < 0.0001). Compared with the Macintosh laryngoscope, the Airtraq laryngoscope provided an improved vocal cord view as assessed by the Cormack and Lehane score (number of patients with Cormack-Lehane scores of 1/2/3/4/37/20/4/3 for the Macintosh, and 65/3/0/0 for the Airtraq laryngoscopes, p < 0.0001). One patient in the Macintosh group had a failed intubation and intubation was achieved with the Airtraq. For obese patients in ramped position, Airtraq affords faster tracheal intubation than the Macintosh laryngoscope.